Peran Restorative Justice Sebagai Alternatif Pemidanaan Anak - Chikita Karunia Samesta Putri; Fildza Shafira Sa’ad; Kanya Tabita Purba Tambak; Dina Amanda (Journal of Constitutional, Law and Human Rights, 2025)
Implementation of restorative justice as an alternative to child punishment in the Juvenile Criminal Justice System (SPPA) based on Law No. 11 of 2012. This approach prioritizes rehabilitation and social reintegration, rather than imprisonment, to protect the best interests of children and reduce negative impacts such as social stigma. Children in conflict with the law require different treatment from adults because their physical, mental, and emotional development is not yet mature. The restorative justice approach involves perpetrators, victims, families, and communities in resolving conflicts through deliberation and recovery. However, its implementation still faces obstacles, such as a lack of understanding from the community and law enforcement. This study uses a normative legal method with a statutory regulatory approach, legal theory, and analysis from expert perspectives. The results of the study indicate that restorative justice is effective in reducing recidivism, supporting social reintegration, and protecting children's rights. In conclusion, the implementation of restorative justice needs to be supported by community education, training for law enforcement officers, and cooperation between families, schools, and communities to ensure that rehabilitation runs optimally and has a positive impact on the future of children.